2018
DOI: 10.3390/en11102685
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Smart Control Method for Electric Vehicle Wireless Charging System

Abstract: In order to shorten the wireless charging time of electric vehicles (EVs) and achieve stable charging, an adaptive smart control method for EV wireless charging is proposed in the paper. The method dynamically tracks the rechargeable battery state during the whole charging process, realizes multi-stage charging of constant current (CC) or constant voltage (CV) by switching two kinds of compensation networks of bilateral L3C and L3C-C, and regulates the charging voltage and current to make it as close as possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Liu et al (2021) investigated the optimal location and tariff of dynamic wireless charging sections for electric vehicles to minimize the total social cost within a given budget. The main problem of the traffic system is to design energy-optimal wireless charging speed control by guiding the vehicle travel speed and rated charging voltage (Gong et al, 2018;Tan et al, 2019). Zhang et al (2021a) designed the location, power, and length of DWC lanes and proposed an ecodriving strategy for electric, connected, and autonomous vehicles to reduce the cost and range of vehicle trips near signalized intersections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al (2021) investigated the optimal location and tariff of dynamic wireless charging sections for electric vehicles to minimize the total social cost within a given budget. The main problem of the traffic system is to design energy-optimal wireless charging speed control by guiding the vehicle travel speed and rated charging voltage (Gong et al, 2018;Tan et al, 2019). Zhang et al (2021a) designed the location, power, and length of DWC lanes and proposed an ecodriving strategy for electric, connected, and autonomous vehicles to reduce the cost and range of vehicle trips near signalized intersections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An adaptive smart control system for EV wireless charging system is presented in (26). The charging method used was based on battery characteristic curves.…”
Section: Control Of Ev Wireless Charging Systemmentioning
confidence: 99%
“…Previous studies have also studied and optimized the output power in the EV-WPT system [15,16]. In a separate study, an adaptive smart control method for EV wireless charging has been proposed to shorten the wireless charging time of electric vehicles (EVs) and achieve stable charging [17]. It has been found that the majority of studies deal with the design and optimization of the charging process under one or several constraints.…”
Section: Introductionmentioning
confidence: 99%